PENINGKATAN KOMPETENSI KADER DAN MONITORING TERHADAP FAKTOR RISIKO PTM (PENYAKIT TIDAK MENULAR) DESA KARANGGINTUNG, KECAMATAN SUMBANG, KABUPATEN BANYUMAS - Gumintang Ratna Ramadhan; Dika Betaditya; Yovita Puri Subardjo; Friska Citra Agustia (Dinamika Journal : Pengabdian Masyarakat, 2019)
Currently there has been a change in causes from infectious diseases to non-communicable diseases (NCD). Posbindu NCD aims to increase community participation in early detection, monitoring and follow-up of NCD risk factors. To be able to achieve these objectives, a large role for cadres is needed. This activity increases the competence of posbindu cadres about the knowledge and skills of posbindu cadres in monitoring risk factors for non-communicable diseases in Karanggintung Village, Sumbang District. The method used in this activity is a participatory method that refers to activities that involve the intended audience for active activities with the aim that an increase in knowledge and special skills in post cadres. Based on the results of evaluations and evaluations that occur skill enhancement is that most cadres are correct in assessing, filling in the monitoring book and having conducted a consultation session. One of the cadres was also quite confident in conducting an assessment using the autocheck tool. Thus, the implementation training in Posbindu Sehat Mulia III Karanggintung Village, Sumbang District, Banyumas Regency, which can improve competence as seen from the cadres knowledge and skills so that it will be improved in optimizing early non-communicable risk factor monitoring.Keywords: cadres, posbindu, non-communicable disease, knowledge, skills